Returning of Hippocampus hippocampus (Linnaeus, 1758) (Syngnathidae) in the Faro Lake – oriented Natural Reserve of Capo Peloro, Italy. Issue 4 (16th February 2020) - Spinelli, Andrea; Capillo, Gioele; Faggio, Caterina; Vitale, Dyana; Spanò, Nunziacarla
Abstract: This study reports the returning of the seahorse in the Faro Lake and the most recent finding in a brackish coastal Mediterranean lagoon. After about 50 years from the first documented occurrence of Hippocampus hippocampus (Linnaeus, 1758) within the "Capo Peloro Lagoons", North East Sicily, two adult specimens were observed alive in 2015. During that time, until the present rediscovery, the species was not recorded in biological studies and censuses for the area. This paper increases the knowledge about both the threatened seahorse species and the Natural Oriented Reserve of Capo Peloro. Graphical Abstract: